2011
DOI: 10.1148/radiol.10100667
|View full text |Cite
|
Sign up to set email alerts
|

Is Apparent Diffusion Coefficient Associated with Clinical Risk Scores for Prostate Cancers that Are Visible on 3-T MR Images?

Abstract: Purpose:To investigate whether apparent diffusion coefficients (ADCs) derived from diffusion-weighted (DW) magnetic resonance (MR) imaging at 3 T correlate with the clinical risk of prostate cancer in patients with tumors that are visible on MR images, with MR imaging/transrectal ultrasonography (US) fusion-guided biopsy as a reference. Materials and Methods:Forty-eight consecutive patients (median age, 60 years; median serum prostate-specifi c antigen value, 6.3 ng/mL) who underwent DW imaging during 3-T MR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
250
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 363 publications
(283 citation statements)
references
References 41 publications
29
250
1
3
Order By: Relevance
“…AUC values for ADC parameters in discriminating low-from intermediateand high-risk lesions (AUC = 0.821-0.854) also lie within the range of previously reported values for peripheral prostate lesions (Donati et al 2014, Kobus et al 2012, Vargas et al 2011, Turkbey et al 2011, Oto et al 2011, Hambrock et al 2011, Peng et al 2013. One recent study reported a higher value of AUC (0.90) for the median ADC in peripheral zone PCas (Hambrock et al 2011).…”
Section: Discussionsupporting
confidence: 83%
“…AUC values for ADC parameters in discriminating low-from intermediateand high-risk lesions (AUC = 0.821-0.854) also lie within the range of previously reported values for peripheral prostate lesions (Donati et al 2014, Kobus et al 2012, Vargas et al 2011, Turkbey et al 2011, Oto et al 2011, Hambrock et al 2011, Peng et al 2013. One recent study reported a higher value of AUC (0.90) for the median ADC in peripheral zone PCas (Hambrock et al 2011).…”
Section: Discussionsupporting
confidence: 83%
“…Although there are strong inverse correlations between ADC and Gleason grade, mpMRI cannot at this time be considered a replacement for biopsy. 58,59 Nevertheless, ADC values can provide useful information in stratifying patient risk prior to biopsy. For instance, a lesion with very low ADC values that is read as a low-grade tumor on biopsy should be considered for rebiopsy based on the high risk of such a lesion harboring a higher-grade tumor.…”
Section: Multiparametric Mri In Active Surveillancementioning
confidence: 99%
“…It was able to be shown that the ADC value has a negative correlation with the Gleason score, i. e., low ADC values are seen primarily in high-grade aggressive prostate cancers [15,18]. Results regarding the ability to differentiate low-grade tumors (Gleason score 3 + 3 = 6) and high-grade tumors (Gleason score > 4 + 3 = 7) in the peripheral zone are very promising since they may be able to help to better determine patient risk potential [19,20]. However since there can still be relevant overlapping of the ADC values in the different Gleason groups, additional studies are needed to implement this grading potential of diffusion-weighted imaging in the clinical routine.…”
Section: Diffusion-weighted Imagingmentioning
confidence: 99%